Delayed presentation of congenital diaphragmatic hernia presenting with intrathoracic gastric volvulus: a case report and review - Nayak, Hemanta K (BMJ Case Rep, 2012)
Acute gastric volvulus associated with congenital diaphragmatic hernia is an unusual surgical emergency and its presentation in adulthood is extremely rare. Gastric volvulus is an uncommon condition which is difficult to diagnose and treat. This case describes a middle aged man presenting with post-traumatic acute abdomen and finally being diagnosed as a case of gastric volvulus due to congenital diaphragmatic hernia which was till now asymptomatic and undiagnosed. Clinical examination and chest x-ray was suggestive of hiatus hernia. Contrast-enhanced CT of thorax and abdomen revealed hiatus hernia and gastric volvulus. A provisional diagnosis of post-traumatic hiatus hernia with associated gastric volvulus was made and was operated on  an emergency basis. Surprisingly, the intraoperative findings revealed significant adhesions near the diaphragm suggestive of congenital diaphragmatic hernia. Hence, a diagnosis of gastric volvulus due to congenital diaphragmatic hernia was made which remained asymptomatic and undiagnosed till adulthood. He responded well to operative management and remained asymptomatic afterwards.